2024
DOI: 10.1021/acs.est.3c06954
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Weight-Dependent Degradation of Plastics: Deciphering Host–Microbiome Synergy Biodegradation of High-Purity Polypropylene Microplastics by Mealworms

Lei He,
Jie Ding,
Shan-Shan Yang
et al.

Abstract: The biodegradation of polypropylene (PP), a highly persistent nonhydrolyzable polymer, by Tenebrio molitor has been confirmed using commercial PP microplastics (MPs) (M n 26.59 and M w 187.12 kDa). This confirmation was based on the reduction of the PP mass, change in molecular weight (MW), and a positive Δδ 13 C in the residual PP. A MW-dependent biodegradation mechanism was investigated using five high-purity PP MPs, classified into low (0.83 and 6.20 kDa), medium (50.40 and 108.0 kDa), and high (575.0 kDa) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
0
0
0
Order By: Relevance
“…molitor larvae modified the gene expression of both their gut bacteria and the larval host to establish a system favorable for plastic degradation when fed PP diets . The larval gut could function as an efficient bioreactor, initiating innate digestive enzymes, defensive mechanisms, and carbohydrate transport to synergistically degrade plastic. , The respective role of gut microorganisms and larval host in modulating the internal environment in response to in vivo MPs biodegradation warrants further in-depth research. Notably, the highest acidification level was observed in the PVC-fed group (6533 ± 189.4 and 7613 ± 266.2), which was significantly ( p < 0.005) higher than those observed in PE-fed and PLA-fed larvae (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…molitor larvae modified the gene expression of both their gut bacteria and the larval host to establish a system favorable for plastic degradation when fed PP diets . The larval gut could function as an efficient bioreactor, initiating innate digestive enzymes, defensive mechanisms, and carbohydrate transport to synergistically degrade plastic. , The respective role of gut microorganisms and larval host in modulating the internal environment in response to in vivo MPs biodegradation warrants further in-depth research. Notably, the highest acidification level was observed in the PVC-fed group (6533 ± 189.4 and 7613 ± 266.2), which was significantly ( p < 0.005) higher than those observed in PE-fed and PLA-fed larvae (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicate that concentrations and distribution of digestive functional enzymes underwent significant alterations in response to the interactions of MPs within this bioreactor in the plastivore insect. Additionally, previous research suggested that lipases, Chitinase, monooxygenase, dioxygenase, and other enzymes may be involved in the degradation and mineralization of different polymers. ,,, Future research should focus on developing highly sensitive biocompatible probes to directly visualize the concentrations and distribution of these enzymes during MP biodegradation processes.…”
Section: Resultsmentioning
confidence: 99%